Al-Seer and Nazar in the Qur’an al-Kareem - Qusay M.Al-Mulla Khalaf,; Zubaida Tariq Ibrahim, (Islamic Sciences Journal, 2025)
ABSTRACT The Glorious Quran highlights the importance of traveling and contemplating together as two means of learning and reflecting Allah's laws for previous nations. Traveling on earth has multiple aspects, including memorization, early arrival, travel, overnight stays, and crossing a small river. The Quran uses imperative and past tense forms, calling for travel and contemplation. Travel is always accompanied by contemplation, as it is the means by which to see and reflect the impacts of previous nations. The Quran uses the rhetorical question in verses about traveling and contemplating to urge people to acknowledge the truth of the fate of those who denied the truth, while indicating the continuity of these laws over time. There is a subtle difference in the relationship between traveling and contemplating, as they are linked by the letters fa' or thumma. Fa' denotes a quick connection and follow-up, while thumma denotes slackness and deliberation, as is evident in the verse of Al-An'am, which requires more contemplation. Commentators also discussed the reasons for choosing the preposition "fi" with "al-sayr," emphasizing that it denotes ease and accessibility on earth for travelling and movement, in contrast to "ala," which denotes height and difficulty. The research plan required dividing it into three sections. The first covered a list of the term and its meaning. The second examined the connotations of the meanings of "al-sayr" and "al-nazr" in the Glorious Quran. The third section examined the lesson behind the coexistence of "al-sayr" and "al-nazr" in the Glorious Quran.